Rethinking Accreditation Policy in Ma'had Aly: Toward a Decolonization of Islamic Higher Education in Indonesia - Arifin, Bustanul; Sulaeman, Mubaidi (Berkala Ilmiah Pendidikan, 2026)
This study critically examines the accreditation policy of Ma’had Aly (traditional Islamic higher education) in Indonesia within the broader discourse of decolonizing Islamic higher education. It aims to assess whether state-regulated accreditation standards, mandated by the Pesantren Law and implemented by the Majelis Masyayikh, align with the foundational epistemological and pedagogical traditions of pesantren. Employing a qualitative research design based on systematic document analysis, the study investigates primary legal sources, including Law No. 18 of 2019, Majelis Masyayikh regulations, and the Minister of Religious Affairs Regulation No. 941 of 2024. These are analyzed alongside seminal scholarly works on Islamic education. The analysis identifies four key findings. First, current accreditation policies heavily prioritize managerial and technocratic indicators such as administrative governance, standardized curricula, and data compliance while marginalizing the intellectual traditions of turats (classical texts) scholarship and embodied pedagogy. Second, the framework exhibits epistemic dependence by adopting Western quality assurance logic focused on institutional documentation and global competitiveness. Third, the system perpetuates colonial legal paradigms, emphasizing documentary legality as the primary basis for institutional legitimacy. Fourth, from a sociological perspective, public trust in Ma’had Aly remains rooted in scholarly lineage (sanad), the authority of the kyai, and intellectual reputation rather than formal accreditation status. Ultimately, the study advocates for a decolonial accreditation framework that authentically integrates discursive traditions, embodied Islamic knowledge, and the traditional scholarly authority of pesantren.